Analisis Kinerja Router Outdoor TP-Link CPE220 dan Mikrotik RouterOS untuk Penerapan Hotspot Nirkabel - Ramadani; Edi Surya Negara (STMIK Budi Darma, 2023)
Outdoor wireless networks refer to communications infrastructure built outdoors, such as in open areas, cities, or large environments. Outdoor wireless networks often use wireless technology to connect devices and provide internet access or communications services to users. One important aspect of outdoor networking is the deployment of appropriate infrastructure. Proper antenna installation and orientation or height are necessary to cover large areas and overcome physical obstacles such as buildings, trees, or uneven terrain. Optimal frequency selection and interference management are also major concerns in optimizing network performance. This research contributes to analyzing and implementing Outdoor Networks (WAN) and Access Points as an effort to increase internet connectivity in remote areas. Through this research, signal quality, range, configuration, data transfer speed and connection reliability will be tested and analyzed. As a result, it is hoped that this research will be able to provide a deeper understanding regarding the effectiveness and efficiency of using outdoor routers in realizing better internet connectivity in rural areas as well as being a consideration in developing technology and internet deployment strategies in remote areas in the future